JENIS MAKROALGA DI PANTAI LHOK BUBON ACEH BARAT - Rita Oktavia; Reza Fitri; Munanda; Dekwan; Ridi Mudika; Novi Afri Yanti (LPPM Universitas Cipta Mandiri, 2025)
An inventory of macroalgae species is crucial for coastal resource development. Macroalgae are known to have several advantages or benefits as raw materials for health, food, and cosmetics. However, the potential of local macroalgae on Lhok Bubon Beach has not been well-published. This descriptive qualitative study aims to identify various macroalgae species found in Lhok Bubon coastal waters. The method used was road sampling. The study population consisted of various macroalgae species found in Lhok Bubon coastal waters, while the study sample consisted of all macroalgae species found within the exploration area. Macroalgae identification was conducted at the Integrated Science Laboratory of Cipta Mandiri University. The identification key from Bold & Michael (1985) was used to determine the names of macroalgae species. The types of macroalgae found on Lhok Bubon Beach include Sargasum sp., Padina australis, Chatomorpha sp., Sargasum natans, Halymenia darvillei, Dictyopteris delicatuta, Gracilaria salicornia, and Boergesenia forbesi. There are two types of macroalgae substrates on Lhok Bubon Beach: sandy and coral rock.